Kesesuaian Operasional Produk Asuransi Syariah dengan Fatwa DSN MUI No:21/DSN-MUI/X/2001 (Studi Kasus AJB Bumiputera 1912 Cabang Surabaya) - Rian Rahmat Hidayat; Irham Zaki (Universitas Airlangga, 2015)
Sharia insurance in Indonesia has experienced a fairly rapid development since the promulgation of MUI fatwa number:21/DSN-MUI/X/2001 about sharia insurance. However, that is still questionable is does the sharia insurance company really run the product operational based on MUI fatwa.This study aims to determine whether product operational of sharia insurance of AJB Bumiputera1912 is in conformity with the sharia rules to follow six indicator akkad, premi, claims, investment, reinsurance, and management of the fund from MUI fatwa or not.The research method is used is a case study with a qualitative descriptive approach. The data used in this study is that the data derived from primary data obtained from fieldwork and secondary data derived from the literature and a wide range of written document. This study using data derived from the management of sharia insurance AJB Bumiputera 1912 in the branch of Surabaya and sharia insurance participants of AJB Bumiputera 1912.The results of this research is operational products of sharia insurance of AJB Bumiputera 1912 were in accordance with Indonesian Ulama Council fatwa DSN Number:21/DSNMUI/X/2001. The suitability reflected from the existence of akkad tabarru’ and akkad tijarah as investment funds (mudharabah), management of premium funds based on sharia, claims fund based on first contract, investment made in accordance with the mandate of participants, then reinsurance process done only to sharia-based reinsurance company.